2012
DOI: 10.1128/iai.05249-11
|View full text |Cite
|
Sign up to set email alerts
|

PPE38 Modulates the Innate Immune Response and Is Required for Mycobacterium marinum Virulence

Abstract: The proline-glutamic acid (PE) and proline-proline-glutamic acid (PPE) family proteins are prevalent in pathogenic mycobacteria and play a diverse role in mycobacterial pathogenesis. While some members have been studied, the function of most PE/PPE proteins remains unknown. In this study, we isolated a transposon-inactivated PPE38 mutant of Mycobacterium marinum and characterized its phenotype. We found that the PPE38 protein is associated with the cell wall and exposed on the cell surface. The inactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 78 publications
(75 reference statements)
3
69
0
Order By: Relevance
“…Alterations in biosynthesis, chain length and functional groups of mycolic acids in mutants of M. bovis BCG, M. tuberculosis and M. marinum caused the loss of the cording phenotype (Dong et al, 2012;Glickman et al, 2000). The need for the presence of a cyclopropane ring in the proximal position of a-mycolic acids for cording was established in one of these studies (Glickman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in biosynthesis, chain length and functional groups of mycolic acids in mutants of M. bovis BCG, M. tuberculosis and M. marinum caused the loss of the cording phenotype (Dong et al, 2012;Glickman et al, 2000). The need for the presence of a cyclopropane ring in the proximal position of a-mycolic acids for cording was established in one of these studies (Glickman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These authors compared the virulent H37Rv and avirulent H37Ra M. tuberculosis strains and found that the formation of cords only occurred in the virulent strain. Later, other researchers working with natural or constructed mutants of M. tuberculosis, M. bovis, M. marinum and M. abscessus reported a decrease in the virulence of mutants that lost cording (Bhatt et al, 2007;Dong et al, 2012;Gao et al, 2003Gao et al, , 2004Glickman et al, 2000;Howard et al, 2006;Makinoshima & Glickman, 2005). In addition, we have demonstrated an increase in the virulence of natural mutants of M. vaccae, M. chubuense, M. gilvum, M. obuense and M. parafortuitum that had acquired the capacity to form microscopic cords (Julián et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adult zebrafish were infected with M. marinum as described previously (27). Briefly, after being anesthetized with 0.1% 3-aminobenzoic acid ethyl ester (tricaine), adult zebrafish were infected by intraperitoneal injection with 10 l of single-cell bacterial suspensions at a dosage of 10 individual strains for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…PPE family protein PPE34 [11], PPE41 [7] and PPE38 [15] were experimentally demonstrated to be cell surface exposed. PPE38 can modulate the host innate immune response via manipulating the production of TNF-α and IL-6 [15]. PPE-SVP subfamily protein Rv1808 has 49% similarity with Mycobacterium avium subsp.…”
Section: Introductionmentioning
confidence: 99%